74.8k views
2 votes
6v+18-9v=-12
solve for v.​

User Gga
by
5.3k points

1 Answer

7 votes

Answer:

v = 10

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

6v + 18 - 9v = -12

Step 2: Solve for v

  1. Combine like terms: -3v + 18 = -12
  2. Isolate v term: -3v = -30
  3. Isolate v: v = 10

Step 3: Check

Plug in v into the original equation to verify it's a solution.

  1. Substitute in v: 6(10) + 18 - 9(10) = -12
  2. Multiply: 60 + 18 - 90 = -12
  3. Add: 78 - 90 = -12
  4. Subtract: -12 = -12

Here we see that -12 does indeed equal -12.

∴ v = 10 is the solution to the equation.

User Ledonter
by
5.8k points